SAFEGUARDING CULTURAL RESOURCES OF BUILT HERITAGE; IDENTIFYING GAPS IN POLICIES AND PRACTICES: A CASE STUDY OF ABBOTTABAD, PAKISTAN. - Adnan Ahmad DOGAR, Syed Wajahat ALI, Ikram SHAH, Faizan Sultan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The identification, preservation and promotion of built heritage is a collective responsibility of Federal, District and local governments along with relevant departments of Sports, Culture, Tourism, Archaeology, and Museums & Youth Affairs. Antiques act of 2016 of Government of KP chalks out a detailed process of identification, preservation, renovation and promotion of cultural heritage. Abbottabad has a rich cultural heritage dating from pre-colonial era but not many sites are included in the list of cultural heritage for the preservation. The study aims to identify the built heritage of cultural significance and then try and understand why these historical remains of cultural significance were not included in the list of cultural heritage by the archaeological department and identify gaps in policy and practices. The study used historical documents, published reports and institutional documents of the local government to identify the sites of cultural significance, interviewed local community in the vicinity of these sites and representatives of local government and interviewed representatives of relevant departments to identify such gaps.